Transient neonatal diabetes mellitus due to de novo mutation in KCNJ11 gene - Kulkarni, Abhishek; Monteiro, Joewin (International Journal of Contemporary Pediatrics, 2025)
Neonatal diabetes mellitus (NDM) is a rare monogenic diabetes that usually presents in first 6 months of life. Activating mutations in KCNJ11 gene encoding Kir6.2 subunit of ATP-sensitive potassium (KATP) channel cause either transient NDM (TNDM) or permanent NDM (PNDM). A month-old male presenting with diabetic ketoacidosis was managed initially with intravenous (IV) fluids and IV insulin administration and subsequently started on subcutaneous insulin therapy on resolution of ketoacidosis. C-peptide level at diagnosis was 0.51 ng/ml and sanger sequencing analysis of the ABCC8, KCNJ11, INS and EIF2AK3 genes identified a heterozygous missense mutation p.R50Q in KCNJ11 gene. Successful transition to oral sulfonylurea therapy was made with maintenance of euglycemia and remission of NDM was witnessed at 5 months of age. A diagnosis of TNDM due to mutation in Kir6.2 subunit of K-ATP channel was made, supervised discontinuation of sulfonylurea therapy performed and the 50 percent risk of relapse of DM during adolescence or adulthood was explained to the family.